Treatment Strategies for the Claudicant - Pereira, Keith (Seminars in Interventional Radiology, 2018)
Peripheral arterial disease (PAD) is a prevalent, morbid, and mortal disease. Claudication represents an early, yet common manifestation of PAD. A clinical history and physical examination combined with an ankle-brachial index can help make a diagnosis of claudication. Due to the polyvascular nature of the underlying atherosclerosis, PAD is often associated with heart disease and stroke. Although health implications of PAD derive from both its limb and cardiovascular manifestations, claudication is life-threatening, less limb-threatening. Medical modification of cardiovascular risk factors and exercise are the cornerstone in the treatment of claudication. Revascularization in claudication is focused at improvement in claudication symptoms and functional status, rather than aggressive attempts at limb salvage. The aim of this article is to summarize the strategies in the treatment of claudication, to serve as a concise and informative reference for physicians who are managing these patients. A framework of the decision-making process in the management of patients with claudication is shown, which can be applied in clinical practice.
Keywords: peripheral arterial disease; claudication; risk factor modification; exercise therapy; revascularization; interventional radiology